Організація і методика податкового контролю великих платників податків - Бруцький, Богдан Олегович; Brutskyy, Bohdan Olehovych (Ірпінь, 2024)
У роботі досліджено напрямки вдосконалення податкового контролю великих платників податків. - розкриття теоретично-методологічних основ здійснення податкового контролю великих платників податків в Україні щодо його сутності, суб’єкта, об’єктів, принципів здійснення; - наведення загальних відомостей про Центральне міжрегіональне управління ДПС по роботі з великими платниками податків та проведення аналізу основних результатів його діяльності; - ознайомлення з організацією контролю великих платників податків в ЦМУ ДПС по роботі з ВПП; - розкриття способів та методів контролю великих платників податків; - наведення результатів контролю великих платників податків в ЦМУ ДПС по роботі з ВПП за 2020-2023 роки; - дослідження напрямків вдосконалення податкового контролю великих платників податків. Базою дослідження виступає Центральне міжрегіональне управління ДПС по роботі з великими платниками податків.

The paper examines directions for improving tax control of large taxpayers. - disclosure of the theoretical and methodological foundations of the implementation of tax control of large taxpayers in Ukraine regarding its essence, subject, objects, principles of implementation; - providing general information about the Central Interregional Administration of the State Tax Service for work with large taxpayers and conducting an analysis of the main results of its activities; - familiarization with the organization of the control of large taxpayers in the CMU DPS on work with the VPP; - disclosure of methods and methods of control of large taxpayers; - providing the results of the control of large taxpayers in the Central Administrative Court of the State of Ukraine on work with the WFP for the years 2020-2023; - research on ways to improve tax control of large taxpayers. The basis of the study is the Central Interregional Administration of the State Tax Service for Work with Large Taxpayers.
Organization and methods of tax control of large taxpayers
Keywords: податковий контроль; великі платники податків; ВПП; ЦМУ ДПС; суб’єкт контролю; об’єкт контролю; принципи здійснення контролю; способи контролю; методи контролю; tax control; large taxpayers; KTU; Centralized State Tax Administration; subject of control; object of control; principles of control; control methods; control methods